Raman studies of MoS2 under strain at different uniaxial directions. (July 2018) - Tan, C.K.; Wong, W.C.; Ng, S.M.; Wong, H.F.; Leung, C.W.; Mak, C.L.
Abstract: Raman spectra of bulk and few layers MoS2 under strain at different uniaxial directions have been measured. MoS2 samples, encapsulated in between polyethylene terephthalate (PET) of octadecagonal shape and a layer of polymethlmethacrylate (PMMA), were bended in order to apply uniaxial tensile strain along different directions of MoS2 . For bulk MoS2, the Raman shift rates of the E 1 2g and A1g modes (the change of the Raman peak position versus strain level) were very small and almost the same for strains applied along different directions. On the other hand, the Raman shift rates of few layers MoS2 were larger than those in bulk MoS2 . In addition, they also exhibited distinctive anisotropic strain responses. On the basis of our results, we believe that the armchair and zigzag directions of the exfoliated MoS2 might be determined by monitoring the variation of Raman shifts of the E 1 2g and A1g modes in different strained directions of MoS2 . Highlights: A modified bending technique has been employed to study the Raman spectra of MoS2 along different strain directions. The Raman shift rates of the quadrilayer MoS2 are sensitive to different applied strain directions. The armchair and zigzag directions of the exfoliated MoS2 might be determined by monitoring the variation of Raman shifts of the E 1 2g and A1g modes in different strained directions.